2023
DOI: 10.1109/access.2023.3330436
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation Using the IC2T Model and Classification of Diabetic Retinopathy Using the Rock Hyrax Swarm-Based Coordination Attention Mechanism

B. N. Jagadesh,
M. Ganesh Karthik,
D. Siri
et al.

Abstract: Diabetic Retinopathy (DR) evaluations are increasingly being automated using artificial intelligence. Diabetes-related retinal vascular disease is a major cause of blindness and visual impairment worldwide. Therefore, automated DR detection devices would greatly aid in reducing visual impairment due to DR through early screening and treatment. Researchers have provided many techniques for picking out abnormalities in retinal images during the past several years. In the past, automated methods for diagnosing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The technique stands very special in balancing computational e ciency and performance. Jagadesh et al [19] suggested a framework that integrated the IC2T model for segmentation with Rock Hyrax swarm-based coordination attention mechanism for classi cation. Their approach has been able to depict the potentials of using bio-inspired algorithms in the enhancement of medical image analysis with improved accuracy.…”
Section: Review Of Existing Models Used For Identi Cation Of Diabetic...mentioning
confidence: 99%
“…The technique stands very special in balancing computational e ciency and performance. Jagadesh et al [19] suggested a framework that integrated the IC2T model for segmentation with Rock Hyrax swarm-based coordination attention mechanism for classi cation. Their approach has been able to depict the potentials of using bio-inspired algorithms in the enhancement of medical image analysis with improved accuracy.…”
Section: Review Of Existing Models Used For Identi Cation Of Diabetic...mentioning
confidence: 99%
“…According to research on breast cancer screening, 20% of women had malignant tumors [7]. Breast tumors may be identified over an extended duration of time by utilizing a number of methods, including X-rays, ultrasound, mammography, magnetic resonance imaging (MRI), positron emission tomography (PET), and computed tomography [8]. Breast cancer in its early stages may be assessed by screening, which finds the disease when small breast symptoms appear.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, the majority of techniques used in the field of ocular diagnostics have been somewhat useful but have limitations in terms of precision and adaptability. Conventional image analysis methods have had difficulty reliably identifying the subtle patterns suggestive of diabetic retinopathy [20] since they are frequently built on singlealgorithm frameworks. This discrepancy results from a deficiency of dynamic flexibility to the various retinal alterations that manifest themselves.…”
Section: Introductionmentioning
confidence: 99%